Compliance with treatment of latent Tuberculosis infection in healthcare workers - Abad, Cybele; Giesler, Joseph; Ircink, Fran; Hla, Mae; Safdar, Nasia (International Journal of Infection Control, 2013)
Healthcare workers are at higher risk of exposure to tuberculosis than the general population and screening upon hire and periodically for latent tuberculosis (TB) infection is required for work in healthcare institutions. Treatment of latent TB infection (LTBI) is strongly recommended in healthcare workers, but despite evidence that shows benefit, the adherence to treatment remains suboptimal. In our retrospective study of healthcare employees at a large, academic, tertiary care institution we found that only 73% were compliant with treatment of LTBI. Side effects and duration of therapy were major reasons for lack of adherence. Closer follow up during the treatment course, and the use of an alternative regimen such as the combination of isoniazid and rifapentine under direct observation for a shorter duration may improve compliance rates in healthcare workers in the future.